Investigation of Generating Systems for a DC Connected Wind Turbine - Agalgaonkar, Yashodhan (My University, 2005)
In this thesis investigations are done to find how much wind power that can be integrated into an existing distribution grid. Steady state voltage changes, flicker emission and thermal limits of lines and transformers are considered as the limiting factors during these investigations. For these investigations, the distribution grid is modelled in the power system simulation software PSS/E®. The modelling is done on the basis of information provided by the relevant distribution company. These investigations are done for different combinations of wind speed and load conditions. In this thesis it is found that steady state voltage changes is generally the factor which restricts the amount of wind power that can be connected at a certain point in the grid provided no bottleneck in the transfer capacity. Reactive power control strategy can be used to integrate more wind power in the grid only when the voltage limits are the deciding factor. In the case of thermal limits of lines or transformer being the deciding factor, it doesn t work. Fault level and consideration of the number of turbines for a given amount of wind power significantly affects the flicker emission value. The results given in this master s thesis can be used to determine the ratings of the wind turbines which can be connected at a certain point while maintaining the voltage limits and power quality in the grid.
Keywords: Elkraftteknik; Electric power engineering